Development as a historical component of the United Nations’ crime policy agenda: From social defence to the Millennium Development Goals - Blaustein, Jarrett (Criminology & criminal justice, 2021)
This article presents a historical analysis of the intellectual and institutional origins of the international community’s interest in the link between crime and development leading up to the adoption of the Millennium Development Goals in 2000. Drawing on a combination of documentary sources and interviews with long-time international crime policy insiders, it traces this interest back to the United Nations’ social defence agenda which emerged in the aftermath of the Second World War. We situate this agenda in relation to the Western aspiration to advance the Modernization project and reflect on how its shortcomings together with ideological, economic and geopolitical shifts at the international level contributed to the diversification of the United Nations’ crime policy agenda during the 1970s. These conditions collectively influenced the international community’s growing concern with crime as an existential threat to economic development during the 1980s. Our analysis highlights how this framing was reinforced by the rise of transnational organized crime as a threat to global capitalism following the collapse of the Soviet Union. It was against this historical backdrop that the United Nations Office for Drug Control and Crime Prevention was established to lead the international community’s fight against ‘uncivil society’. We conclude by reflecting on United Nations Office for Drug Control and Crime Prevention’s tumultuous early years along with the omission of ‘crime’ from the Millennium Development Goals and suggest that these conditions, along with the adoption of the United Nations Conventions Against Transnational Organized Crime and Corruption, set the stage for the organization’s future advocacy for the inclusion of crime in the Sustainable Development Goals.